Omnichannel Strategy and Consumer Behavior in Distribution Channels: Trends in the Ophthalmology Sector - Rivero Gutiérrez, Lourdes; Samino García, Rocio (Frontiers in Psychology, 2020)
Changes in consumer behavior are forcing companies to rapidly shift their distribution channels toward an omnichannel model. In the case of the ophthalmology sector, however, the purchase of contact lenses and prescription glasses requires professional examination by a trained eye specialist. This peculiarity of the sector affects the shift toward omnichannel. This paper is novel in that it addresses a research gap by studying the distribution channels for regulated products and services such as health products that required a closer professional service. This paper addresses the transformation of companies towards an omnichannel model using a common scientific forecasting method (i.e., the Delphi method) to identify trends and problems. In this scenario of high complexity and uncertainty where there is insufficient relevant quantitative information for decision making, the Delphi method is applied to ensure a consensual decision-making process. Consensus was reached by a panel of 11 experts on the Spanish ophthalmology sector after three rounds of questioning. The final set of indicators involve 19 different criteria grouped into four categories (1) current situation of the distribution channel, (2) changes in distribution channels, (3) trends and near future of the distribution channel, and (4) consequences and adaptations for supply chain agents. The results from each round of consultation were then analysed by means of statistical analysis with SPSS and discussed for each category. The results confirm that traditional intermediaries face difficulties to avoid being squeezed out of the sector because of shortening distribution channels and the entry of new online intermediaries with service integration models. We identify future scenarios and define actions that different agents can take to enhance their competitiveness in the short and long term. The arrival of omnichannel distribution is inevitable in the ophthalmology sector, entailing a major transformation from a rigid traditional distribution model to a more complex and flexible model following the entry of new online intermediaries.